Populasi dan Sampel dalam Penelitian Pendidikan: Memahami Perbedaan, Implikasi, dan Strategi Pemilihan yang Tepat - Mardhiyah Mardhiyah; Nur Afni Dinilhaq; Yona Amelia; Adelia Arini; Rully Hidayatullah; Harmonedi Harmonedi (Lembag, 2025)
Educational research requires a thorough understanding of population and sample concepts as the foundation for ensuring the validity and generalizability of findings. This article explores the fundamental differences between population and sample, the implications of their selection on research outcomes, and appropriate strategies for selecting a representative sample. By reviewing commonly used sampling approaches, such as probability and non-probability techniques, this paper highlights the importance of aligning the method with the research objectives and context. A clear understanding of these concepts is crucial for researchers to produce accurate, reliable, and contextually relevant educational data.